Education Policy: Understanding Policy Analysis in the Education Sector in Indonesia - Deding Ishak (Sean Institute, 2024)
This research aims to explore and analyze education policies in Indonesia to understand the impacts, challenges and potential improvements in the national education system. This research uses a qualitative approach with descriptive methods. The research results indicate that methods and formulations in formulating education policies in Indonesia play a central role in successful implementation in the field. The importance of selecting methods that involve in-depth analysis of the social, economic and cultural context of society is a determining factor in creating responsive and relevant policies. Synergy between government, educational institutions, community leaders, and education experts provides the basis for integrated education policies, ensuring harmony between key components such as curriculum, teaching methods, and assessment. Along with that, the research results also highlight the importance of prospective, retrospective, and integrated policy analysis as instruments for predicting policy impacts before implementation, understanding policy impacts after implementation, and creating responsive and sustainable policies in the face of changing social and economic dynamics.